Ni-W bimetallic catalyst and preparation method and application thereof
By preparing Ni-W bimetallic catalysts, hydrothermal reaction and heat treatment methods were used to form a nanoflower-like structure, which solved the problem of insufficient adsorption capacity and activity of nickel-based catalysts, significantly improved the conversion rate of 5-hydroxymethylfurfural and the yield of 2,5-furandicarboxylic acid, and achieved efficient electrocatalytic oxidation reaction.
Patent Information
- Application Number
- CN202510014111.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-06
AI Technical Summary
The existing nickel-based catalysts have weak adsorption ability to 5-hydroxymethylfurfural and have poor intrinsic activity of metal sites, resulting in low yield and Faraday efficiency of electrocatalytic oxidation to form 2,5-furandicarboxylic acid.
By preparing Ni-W bimetallic catalyst, hydrothermal reaction and heat treatment methods are used to form a nanoflower-like structure, the surface of single atom tungsten and metal defects are co-modified, and the Ni-W solid solution forms a body phase to enhance catalytic activity.
The conversion rate of 5-hydroxymethylfurfural and the yield of 2,5-furandicarboxylic acid are significantly improved, Faraday efficiency is improved, and an efficient electrocatalytic oxidation reaction is achieved.
Smart Images

Figure CN119824465A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically relates to a Ni-W bimetallic catalyst and a preparation method and application thereof. Background Art
[0002] Compared with the traditional thermal catalytic conversion of 5-hydroxymethylfurfural (HMF), the HMF electro-oxidation reaction in aqueous solution shows significant advantages, including avoiding high temperature and high pressure environment, replacing organic solvent with water phase, high energy utilization rate, precise voltage control of the reaction process, green environmental protection and other characteristics, which reduce environmental pollution.
[0003] In recent years, precious metal catalysts such as gold, palladium, and platinum, as well as transition metal catalysts such as iron, cobalt, and nickel have been widely used in the catalytic system of HMF electro-oxidation. However, due to the high cost of precious metal catalysts and the insufficient activity of transition metal catalysts, considering the economic benefits and catalytic effects, most of the catalysts designed so far are not satisfactory. Nickel-based catalysts have excellent physicochemical properties and flexible and adjustable electronic structures, and are currently widely studied transition metal materials. In practical applications, nickel-based catalysts have weak adsorption of HMF and poor intrinsic activity of metal sites, resulting in low yield and Faradaic efficiency of electrocatalytic oxidation of HMF to obtain 2,5-furandicarboxylic acid (FDCA). In order to improve the performance of nickel-based catalysts, researchers introduced doping metals such as Co, Fe, and Cu to optimize the coordination environment of Ni sites and adjust the electronic state of Ni to improve the kinetics of the reaction sites. Wang et al. introduced W to regulate the electronic structure of Ni, and prepared Ni-WOx catalyst by coprecipitation method for urea electrocatalytic oxidation. The incorporation of high-valent W promoted the generation of high intrinsic active sites, which was nearly doubled compared to NiOx catalyst performance, showing the catalytic potential of Ni-W system (Angew.Chem.Int.Ed.2021,60,10577.). Hu et al. prepared a three-dimensional porous WO3 / Ni electrode by one-step hydrothermal method for HMF oxidation, but due to the single structure, the yield and Faraday efficiency were low (Molecular Catalysis, 2021,504,111459.). At present, the challenges of weak adsorption capacity and slow kinetics of reaction substrates in 5-hydroxymethylfurfural oxidation reaction (HMFOR) have not been solved. For catalytic sites in a single coordination environment, it is difficult to have both favorable adsorption sites and highly active catalytic sites. Summary of the invention
[0004] The purpose of the present invention is to provide a Ni-W bimetallic catalyst and a preparation method and application thereof in order to solve the above problems, aiming to solve the problems in the prior art.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] The present invention provides a method for preparing a Ni-W bimetallic catalyst, comprising the following steps:
[0007] Step 1: dissolving soluble nickel salt, soluble tungsten salt, urea and ammonium fluoride in water to form a precursor solution;
[0008] Step 2: Using carbon paper as a carrier, immersing it in the precursor solution obtained in step 1, and hydrothermally reacting the catalyst to grow on the carbon paper;
[0009] Step 3: heat-treating the catalyst-loaded carbon paper obtained in step 2 under a nitrogen atmosphere to prepare a Ni-W bimetallic catalyst.
[0010] As a further optimization scheme of the present invention, the morphology of the Ni-W bimetallic catalyst is nanoflower-like.
[0011] As a further optimization scheme of the present invention, the soluble nickel salt is at least one of nickel nitrate, nickel chloride and nickel sulfate.
[0012] As a further optimization scheme of the present invention, the soluble tungsten salt is sodium tungstate.
[0013] As a further optimization scheme of the present invention, in the precursor solution, the molar ratio of Ni to W is 100:3 to 100:30.
[0014] As a further optimization scheme of the present invention, the temperature of the hydrothermal reaction is 100-130° C., and the time is 5-7 hours.
[0015] As a further optimization scheme of the present invention, the heat treatment is carried out in a nitrogen atmosphere at a heating rate of 1 to 2°C / min, the heat treatment temperature is 400 to 450°C, and the time is 2 to 3 hours.
[0016] The present invention also provides a Ni-W bimetallic catalyst, which is prepared by the above-mentioned preparation method. The Ni-W bimetallic catalyst consists of a surface co-modified by single-atom tungsten and metal defects and a Ni-W solid solution phase.
[0017] The invention also provides an application of a Ni-W bimetallic catalyst in the electrocatalytic oxidation of 5-hydroxymethylfurfural (HMF) to prepare 2,5-furandicarboxylic acid (FDCA).
[0018] As a further optimization scheme of the present invention, the preparation is specifically as follows: placing the constructed three-electrode system into an electrolyte, applying an electric field, and obtaining FDCA; wherein the three-electrode system includes a working electrode containing the Ni-W bimetallic catalyst, a Hg / HgO reference electrode, and a platinum counter electrode, the electrolyte includes an anolyte KOH+HMF and a cathode electrolyte KOH, the electric field voltage is 1.0-1.7V, and the catalytic time is 1-5h.
[0019] The beneficial effects of the present invention are:
[0020] 1) The Ni-W bimetallic catalyst of the present invention exhibits a nanoflower morphology, exposing more reactive sites. The surface of the Ni-W bimetallic catalyst co-modified with single-atom tungsten and metal defects can enhance the adsorption of 5-hydroxymethylfurfural (HMF), and the bulk phase composed of the Ni-W solid solution induces the generation of more active sites, greatly improving the overall catalytic activity, and achieving high HMF conversion rate, high 2,5-furandicarboxylic acid (FDCA) yield and high Faraday efficiency;
[0021] 2) The surface of the Ni-W bimetallic catalyst of the present invention is co-modified by single atomic tungsten and metal defects, and the bulk phase is composed of a Ni-W solid solution. This structure constructs adsorption sites that can enrich 5-hydroxymethylfurfural and kinetically more powerful catalytic sites, thereby improving the overall catalytic activity and synergistically improving the performance of 5-hydroxymethylfurfural electrooxidation to produce 2,5-furandicarboxylic acid in terms of both thermodynamics and kinetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a scanning electron microscope image of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention.
[0023] Figure 2 It is a transmission electron microscope image of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention.
[0024] Figure 3 It is a scanning transmission electron microscope image of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention.
[0025] Figure 4 It is a scanning transmission electron microscope image and an energy dispersion spectrum image of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention.
[0026] Figure 5 It is a linear sweep voltammogram of HMFOR of a series of Ni-W bimetallic catalysts prepared in Examples 1-7 of the present invention and NiO of Comparative Example 1 in 1 M KOH + 10 mM HMF.
[0027] Figure 6 1 is the X-ray diffraction pattern of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention and the NiO of Comparative Example 1.
[0028] Figure 7 It is the ultraviolet-visible spectra of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention and the NiO of Comparative Example 1.
[0029] Figure 8 1 and 2 are open circuit potential diagrams of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention and the NiO of Comparative Example 1 in 1M KOH and 1M KOH+10mM HMF solutions, respectively.
[0030] Fig. 9 It is a linear sweep voltammogram of OER and HMFOR of the Ni-W bimetallic catalyst prepared in Example 1 of the present invention in 1M KO H and 1M KOH+10mM HMF solution.
[0031] Fig.10 Graph showing conversion rate, yield and Faraday efficiency of seven cycles of electrocatalytic oxidation of HMF to produce FDCA using the Ni-W bimetallic catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0032] The present application is further described in detail below in conjunction with the accompanying drawings. It is necessary to point out here that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technical personnel in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0033] 1. Materials
[0034] Unless otherwise specified, the methods used in this application are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0035] 2. Methods
[0036] Example 1
[0037] A method for preparing a Ni-W bimetallic catalyst, in this embodiment, the molar ratio of Ni:W in the precursor solution is 10:1 (equivalent to 100:10), comprising the following steps:
[0038] (1) Carbon paper pretreatment: A 1 mm thick carbon paper was cut into a size of 1 cm × 2 cm, and ultrasonically treated with 3 M HCl solution, acetone, ethanol, and distilled water for 30 min in sequence to remove the surface oxide layer and organic matter. Finally, it was repeatedly washed with distilled water for several times and dried in a vacuum drying oven to obtain the treated carbon paper, which was used as the electrode substrate for the subsequent growth of the catalyst.
[0039] (2) Preparing a precursor solution: 1.06 g Ni(NO3)2·6H2O, 0.96 g CO(NH2)2 and 0.3 g NH4F were dispersed in deionized water (60 mL) to form liquid A; 120 mg Na2WO4·2H2O was dissolved in deionized water (20 mL) to form liquid B, and then ultrasonicated for 5 min, and then liquid B was injected into liquid A and stirred for 60 min to form a precursor solution;
[0040] (3) Hydrothermal reaction: The above precursor solution and a cleaned carbon paper (1 cm × 2 cm) were transferred into a 100 mL Teflon-lined stainless steel autoclave; then, the autoclave was sealed and placed in an oven at 120 °C for 5 h; after the autoclave was cooled to room temperature, the carbon paper was taken out, washed several times with deionized water and ethanol, respectively, and dried at 60 °C in vacuum for 5 h;
[0041] (4) Heat treatment: The catalyst-loaded carbon paper was placed in a tube furnace, nitrogen was introduced, and the temperature was raised to 400°C at a rate of 1°C / min, and then placed at this temperature for 2 h. The prepared Ni-W bimetallic catalyst was denoted as W1-Ni 1-x O / NiWO(-10), abbreviated as W1-Ni 1-x O / NiWO.
[0042] Note: x indicates that the metal Ni site has an unknown amount of missing metal.
[0043] Example 2
[0044] In this embodiment, the preparation method is the same as that in embodiment 1, except that the content of Na2WO4·2H2O in the precursor solution is changed to 36 mg, the molar ratio of Ni:W in the precursor solution is 100:3, and the catalyst is recorded as W1-Ni 1-x O / NiWO-3.
[0045] Example 3
[0046] In this embodiment, the preparation method is the same as that in embodiment 1, except that the content of Na2WO4·2H2O in the precursor solution is changed to 60 mg, the molar ratio of Ni:W in the precursor solution is 100:5, and the catalyst is recorded as W1-Ni 1-x O / NiWO-5.
[0047] Example 4
[0048] In this embodiment, the preparation method is the same as that in embodiment 1, except that the content of Na2WO4·2H2O in the precursor solution is changed to 84 mg, the molar ratio of Ni:W in the precursor solution is 100:7, and the catalyst is recorded as W1-Ni 1-x O / NiWO-7.
[0049] Example 5
[0050] In this embodiment, the preparation method is the same as that in embodiment 1, except that the content of Na2WO4·2H2O in the precursor solution is changed to 180 mg, the molar ratio of Ni:W in the precursor solution is 100:15, and the catalyst is recorded as W1-Ni 1-x O / NiWO-15.
[0051] Example 6
[0052] In this embodiment, the preparation method is the same as that in embodiment 1, except that the content of Na2WO4·2H2O in the precursor solution is changed to 240 mg, the molar ratio of Ni:W in the precursor solution is 100:20, and the catalyst is recorded as W1-Ni 1-x O / NiWO-20.
[0053] Example 7
[0054] In this embodiment, the preparation method is the same as that in embodiment 1, except that the content of Na2WO4·2H2O in the precursor solution is changed to 360 mg, the molar ratio of Ni:W in the precursor solution is 100:30, and the catalyst is recorded as W1-Ni 1-x O / NiWO-30.
[0055] Example 8
[0056] In this embodiment, the preparation method is the same as that in Embodiment 1, except that 1.06 g Ni(NO3)2·6H2O in the precursor solution is replaced by 0.87 g NiCl2·6H2O, and the molar ratio of Ni:W in the precursor solution is 10:1, which is consistent with Embodiment 1.
[0057] Example 9
[0058] In this embodiment, the preparation method is the same as that in Embodiment 1, except that 1.06 g Ni(NO3)2·6H2O in the precursor solution is changed to 1.03 g NiSO4·7H2O, and the molar ratio of Ni:W in the precursor solution is 10:1, which is consistent with Embodiment 1.
[0059] Comparative Example 1
[0060] In this comparative example, the preparation method is the same as that in Example 1, and the only difference from Example 1 is that sodium tungstate is not added to the precursor solution of this comparative example, and the prepared catalyst is recorded as NiO.
[0061] Comparative Example 2
[0062] In this comparative example, the preparation method is the same as that in Example 1, and the only difference from Example 1 is that 120 mg Na2WO4·2H2O in the precursor solution of this comparative example is replaced by 88 mg (NH4)6H2W 12 O 40 xH2O, maintaining the N:W molar ratio in the precursor solution at 10:1, which is consistent with Example 1.
[0063] Comparative Example 3
[0064] In this comparative example, the preparation method is the same as that in Example 1, and the only difference from Example 1 is that the heat treatment atmosphere is changed to air.
[0065] Comparative Example 4
[0066] In this comparative example, the preparation method is the same as that in Example 1, and the only difference from Example 1 is that the heat treatment atmosphere is changed to ammonia.
[0067] The catalysts prepared above were characterized and analyzed by scanning electron microscopy (SEM), transmission electron microscopy (TEM), high-angle annular dark field scanning transmission electron microscopy (HADDF-STEM), elemental mapping (EDS), X-ray diffractometer (XRD) and ultraviolet visible spectrophotometer (Uv-Vis), as follows:
[0068] Figure 1 and Figure 2 The catalyst W1-Ni of Example 1 is respectively 1-x Scanning electron microscopy and transmission electron microscopy images of O / NiWO; Figure 1-2 As shown, the catalyst of Example 1 exhibits a nanoflower morphology with thinner edge nanosheets;
[0069] Figure 3 The catalyst W1-Ni of Example 1 1-x Scanning transmission electron micrograph of O / NiWO; according to the difference in atomic contrast, the brighter and more scattered bright spots are single W atoms, the bright spots with slightly lower brightness and regular arrangement are the entire array of Ni atoms, and the black voids in the atomic phase are metal defects, such as Figure 3 As shown, there are abundant tungsten single atoms and metal defects on the surface of the catalyst sample of Example 1;
[0070] Figure 4 The catalyst W1-Ni of Example 11-x Scanning transmission electron microscopy and energy dispersion spectrum of O / NiWO; Figure 4 As shown, Ni, W, and O on the surface of the catalyst sample of Example 1 are uniformly distributed, and W atoms are not agglomerated, which proves that W exists in the form of single atoms on the catalyst surface.
[0071] Performance test: The electrochemical performance of the catalyst was tested by a three-electrode system. All tests were carried out in an H-type electrolytic cell. The carbon paper was fixed with an electrode clip so that its effective exposure area was 1×1.5 cm 2 , it was used as the working electrode, and the Hg / HgO electrode and the platinum electrode were used as the reference electrode and the counter electrode respectively, and the H-type electrolytic cell with the anode and cathode chambers separated by the DuPont proton exchange membrane (Nafion-117) was used. The electrolytes in the cathode chamber and the anode chamber were both 1M KOH solutions. During the test, 10mmol / L HMF was added to the anode chamber. The scanning range of the linear sweep voltammetry curve was 1.0-1.7V, and the scanning range of the cyclic voltammetry curve was 0.52-1.72V, and the scanning rate was 5mv / s, as follows:
[0072] Figure 5 The NiO prepared in Comparative Example 1 and the tungsten-containing catalyst W1-Ni prepared in Examples 1-7 1-x Comparison of linear sweep voltammetric curves of O / NiWO-X' (X' = 3, 5, 7, 10, 15, 20, 30); Figure 5 It can be seen that compared with pure NiO, W1-Ni doped with W 1-x The HMF electrocatalytic oxidation performance of O / NiWO-X' catalysts was improved; the W1-Ni 1-x O / NiWO-10 catalyst has the best HMF electrocatalytic performance, with a lower starting point and a larger current density.
[0073] Figure 6 NiO and W1-Ni 1-x X-ray diffraction pattern of O / NiWO; Figure 6 It can be seen that compared with NiO, W1-Ni 1-x New diffraction peaks appeared in O / NiWO. The explanation for this is that after W doping, part of the Ni in the original NiO unit cell was replaced by W to form a Ni-W solid solution. Ni and W in the solid solution were arranged regularly, thus generating new XRD diffraction peaks. The new peaks shifted to different degrees compared with the diffraction peaks of NiO, thus proving that W1-Ni 1-xIn addition to modifying the catalyst surface, the tungsten in O / NiWO also doped the bulk phase and optimized the overall structure of the catalyst. That is, the Ni-W bimetallic catalyst prepared in the present application consists of a surface co-modified with single atomic tungsten and metal defects and a Ni-W solid solution bulk phase.
[0074] Figure 7 NiO and W1-Ni 1-x UV-visible spectrum of O / NiWO; Figure 7 As shown, compared with pure NiO, W1-Ni 1-x O / NiWO greatly reduces the band gap width of the material, improves the conductivity, and makes it easier for electrons to jump and participate in the reaction.
[0075] Figure 8 NiO and W1-Ni 1-x The open circuit potential curves of W1-NiWO in 1M KOH and 1M KOH+10mM HMF solutions respectively; Compared with NiO, W1-Ni 1-x O / NiWO exhibits a larger open circuit potential difference △OCP after adding HMF, indicating that it has a stronger HMF adsorption capacity.
[0076] Fig. 9 W1-Ni 1-x Linear sweep voltammograms of OER (oxygen evolution reaction) and HMFOR (5-hydroxymethylfurfural oxidation reaction) of O / NiWO in 1M KOH and 1M KOH+10mM HMF solutions; 1-x O / NiWO has high activity for HMF electrocatalytic oxidation but low activity for OER, which ensures that the competitive side reactions during HMF oxidation are very weak and maintains a high Faradaic efficiency of the reaction.
[0077] Fig.10 W1-Ni 1-x The HMF conversion rate, yield and Faraday efficiency of the seven cycles of HMF electrocatalytic oxidation of HMF to prepare FDCA on O / NiWO; it shows that the W1-NiWO prepared in Example 1 1-x O / NiWO can have high HMF conversion, high yield, high Faradaic efficiency and high stability.
[0078] The catalysts prepared in Examples 1, 8, 9 and Comparative Examples 1-4 were used to electrocatalytically oxidize HMF to prepare FDCA. The experimental conditions and HMF conversion rate, yield and Faraday efficiency records are shown in Table 1:
[0079] Table 1
[0080]
[0081] Experimental conclusion: The HMF conversion rate, FDCA yield and Faraday efficiency of Examples 1, 8, 9 and Comparative Examples 1-4 are shown in the table above. It can be seen that the Ni-W bimetallic catalysts prepared according to this experimental method all exhibit superior performance than pure NiO, reflecting the universality of the preparation method; among them, the catalyst performance using Ni(NO3)2·6H2O and Na2WO4·2H2O as Ni source and W source is the best; in addition, the influence of heat treatment atmosphere on material properties is more significant. The catalyst obtained by heat treatment under nitrogen atmosphere has the best effect, while the yield and Faraday efficiency of the catalyst obtained under air and ammonia cannot reach the effect under nitrogen atmosphere.
[0082] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a Ni-W bimetallic catalyst, characterized in that: The following steps are involved: Step 1: dissolving soluble nickel salt, soluble tungsten salt, urea and ammonium fluoride in water to form a precursor solution; Step 2: Using carbon paper as a carrier, immersing it in the precursor solution obtained in step 1, and hydrothermally reacting the catalyst to grow on the carbon paper; Step 3: heat-treating the catalyst-loaded carbon paper obtained in step 2 under a nitrogen atmosphere to prepare a Ni-W bimetallic catalyst.
2. The method for preparing a Ni-W bimetallic catalyst according to claim 1, characterized in that: The Ni-W bimetallic catalyst has a nano-flower morphology.
3. The method for preparing a Ni-W bimetallic catalyst according to claim 1, characterized in that: The soluble nickel salt is at least one of nickel nitrate, nickel chloride and nickel sulfate.
4. The method for preparing a Ni-W bimetallic catalyst according to claim 1, characterized in that: The soluble tungsten salt is sodium tungstate.
5. The method for preparing a Ni-W bimetallic catalyst according to claim 1, characterized in that: In the precursor solution, the molar ratio of Ni to W is 100:3 to 100:
30.
6. The method for preparing a Ni-W bimetallic catalyst according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-130° C. and the time is 5-7 hours.
7. The method for preparing a Ni-W bimetallic catalyst according to claim 1, characterized in that: The heat treatment is carried out in a nitrogen atmosphere at a heating rate of 1 to 2° C. / min, the heat treatment temperature is 400 to 450° C., and the time is 2 to 3 hours.
8. A Ni-W bimetallic catalyst, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.
9. Use of the Ni-W bimetallic catalyst as claimed in claim 8 in the electrocatalytic oxidation of 5-hydroxymethylfurfural to produce 2,5-furandicarboxylic acid.
10. The use according to claim 9, characterized in that: The preparation is specifically as follows: placing the constructed three-electrode system into an electrolyte, applying an electric field, and obtaining FDCA; wherein the three-electrode system includes a working electrode containing the Ni-W bimetallic catalyst, a Hg / HgO reference electrode, and a platinum counter electrode, the electrolyte includes an anolyte KOH+HMF and a catholyte KOH, the electric field voltage is 1.0-1.7V, and the catalytic time is 1-5h.
Citation Information
Patent Citations
Method for preparing nickel-tungsten bimetallic carbide catalyst by organic-inorganic hybrid route and application of nickel-tungsten bimetallic carbide catalyst
CN107511159A
Preparation method of nickel-tungsten composite electrode and application of nickel-tungsten composite electrode in electrocatalytic oxidation
CN114737215A
Method for electrocatalytic oxidation of 5-hydroxymethylfurfural by nickel-molybdenum bimetallic catalyst
CN116377495A
Nickel-molybdenum bimetallic catalyst and preparation method and application thereof
CN119162606A